Tuberculosis is still the most Common Cause of Mediastinal and Intra-abdominal Lymphadenopathy by EUS-FNA in India - Behera, Manas Kumar; Narayan, Jimmy; Agarwal, Shobhit; Mishra, Debakanta; Reddy, Pruthvi; Singh, Ayaskanta; Pati, Girish Kumar; Sahu, Manoj Kumar (Journal of Digestive Endoscopy, 2021)
Background Lymph nodal tuberculosis is reported to occur in 4% to 7% of all tuberculosis, and mediastinal lymphadenopathy accounts for 10% of lymph nodal tuberculosis but the diagnosis still remains a challenge due to inaccessibility to these sites. There is a scarcity of recent data from India about the etiology of intra-abdominal and mediastinal lymphadenopathy despite being frequently detected in cross-sectional imaging.Methods A retrospective study was conducted after reviewing hospital records over a period of 3 years from December 2017 to December 2020 who underwent endoscopic ultrasonography (EUS). A total of 126 patients with mediastinal and/or intra-abdominal lymphadenopathy detected by cross-sectional imaging were examined for clinical features, EUS, and histopathology records.Results The mean age of patients was 53.12 ± 14.15 years. Seventy-one patients (56%) had intra-abdominal lymph nodes and 55 (44%) had mediastinal lymph nodes. The average number of needle passes was 2.35 ± 0.58 (range: 2–4). The majority of patients had tubercular etiology (53.2%) followed by metastatic (26.2%). Other etiologies were reactive (4.8%), lymphoma (4.8%), sarcoidosis (3.2%), and GIST (1.6%). No diagnosis could be ascertained in 6.3% of patients. The EUS features that favored tubercular etiology over metastatic were heterogeneous echotexture (72% vs. 30%), irregular shape (78% vs. 12%), indistinct borders (81% vs. 30%) and calcification (43% vs. 15%). Partial anechoic area and hyperechoic area were seen in 21% and 64% of tubercular patients, respectively. EUS only had sensitivity and specificity of 63% and 84%, respectively, and EUS FNA had a very high sensitivity and specificity of 93% and 100%, respectively.Conclusion Tuberculosis is still the most common cause of lymph nodes. EUS FNA had a very high sensitivity and specificity of 93% and 100%, respectively, for the diagnosis of mediastinal and intra-abdominal lymphadenopathy.
Keywords: tuberculosis; EUS; lymph nodes